Application Of Swot Analysis To Pt Xyz's Performance Improvement Strategy In Marketing And Customer Service Division - Salma Putria Nabila; Akmal Suryadi (International Journal of Mechanical, Industrial and Control Systems Engineering, 2024)
This study aims to analyze the strategy of improving employee performance at PT XYZ, a state-owned company that plays a vital role in the provision of electricity in Indonesia. In the context of increasingly fierce competition and increasing customer demands, SWOT analysis is used to identify the strengths, weaknesses, opportunities, and threats facing companies. The results of the analysis show that internal strengths, such as technical expertise, can be leveraged to develop more innovative products and services. This study also emphasizes the importance of improving service quality as a key factor in increasing customer satisfaction. Thus, the recommendations produced are expected to assist PT XYZ in formulating an effective strategy to achieve its business goals. The results of this research make a significant contribution to the development of human resources and the improvement of company performance.